Development of an inexpensive data logger for solar water heating system regulators - Ait ahmed Wassima; Aggour Mohammed; Ouhammou Badr (Institute of Advanced Engineering and Science, 2019)
Each solar thermal plant can provide different parameters to be treated and evaluated, mostly temperature measurements, pressure specifications, heat transfer values. This data collection can be quite expensive taking into account the important number of sensors and data loggers and their specifications. Hence to assure flexibility in the data collection at a low cost, many hardware and software specifications can be adopted. Here we built an inexpensive data logger based on the Arduino board and IDE to collect and store incoming data from Resol DeltaSol regulators integrated in different solar water heating systems. The objective of this study is to allow massive synchronized measurements with high resolution to be stored into an SD card through the Arduino platform. The measurements are given by multiple sensors (temperature, pump speed, relay states) connected to the regulator. The results from the tests of the plant connected to the data logger are provided later on, alongside the commercial aspects of the built data logging device. After a month of daily measurements, the data logger showed an outstanding performance with an extreme low cost compared to industrial datalogger.